Relationship between noise and job stress at a private thread spinning company - Mursali, Andi; Basuki, Endang; Dharmono, Suryo (Universa Medicina, 2009)
Noise exposure is one of the major occupational hazards in many places, and has several health effects, including hearing loss and psychological effects such as sleep disturbances and mental stress. The objective of this research was to determine the relationship between noise and stress and other risk factors that affect job stress. A cross-sectional comparative design involved a total of 326 workers consisting of 220 workers in high noise conditions and 106 workers in low noise conditions. The data were collected directly from the respondents by filling out the questionnaire on worker characteristics, the stress diagnostic questionnaire, and the symptom checklist 90, through discussions with company management, and by measurement of noise levels. The job stress prevalence in workers in high noise conditions was 55% and in those in low noise conditions 24.5%. The results showed that risk factors such as gender of workers, noise conditions, habitual use of ear plugs, shift work, and work stressors had a significant relationship with job stress. Multivariate analysis indicated that the habit of using earplugs was a dominant risk factor causing job stress. The prevalence of job stress in high noise conditions was higher than that in workers in low noise conditions. Noise conditions have a significant relationship with job stress (OR=2.46; 95% CI 1.33 - 4.55). Workers in high noise conditions who did not always use or never had used ear plugs had a higher chance of experiencing stress than those in low noise conditions who did not need ear plugs (OR=21.76; 95% CI 8.09 - 58.52). This study supported that noise exerts its health effect via stress, since noise often raise stress in various ways.